INFEKSI VIRUS RABIES DI ANAK-ANAK - A.A.N. Subawa; DGD. Dharma Santhi; A.A Raka Sudewi; IWP. Sutirta Yasa (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Rabies has been known in ancient Egypt and China since the fifth century. The disease is caused by the Rhabdovirus of the genusLyssavirus spread from animals or bats to humans by saliva. A five-year-old kid was admitted to Sanglah General Hospital on February19. 2010 with fever complaints, before admitted to the hospital, since the morning he always stuck out his tongue, bit his lips, drinkinga little of water and hard to swallow. From the anamnesis, it is known that the patient has a history of bitten by a dog on February 4.2010 at the lower eyelid and had received wound treatment and VAR, after a while having the treatment the patient eventually died onFebruary 21. 2010. According to the post-mortem sample of the LCS it is showed a positive PCR result of rabies virus infection.